From the centre to the margins: German-speaking scholarship on Matthew’s Gospel as a case study for Matthean scholarship as a whole - Deines, Roland (2009)
Matthean scholarship was once a booming discipline and one of the centres of New Testament research; it’s probably not just biased prejudice when a German claims that the initial thrust behind the heyday of Matthean scholarship in the early second half of the 20th century came from German scholars such as Bornkamm, Frankemölle, Hummel, Strecker, Walker and many more. Since then, however, it appears that these former glories have largely vanished: Matthean studies have relinquished their prominence within the study of the New Testament and the understanding of early Christianity.